Ghana must go - Selasi, Taiye (Penguin Press, 2013)
"Kweku Sai is dead. A renowned surgeon and failed husband, he succumbs suddenly at dawn outside his home in suburban Accra. The news of Kweku's death sends a ripple around the world, bringing together the family he abandoned years before"--Dust jacket flap.